Pengaruh Semangat Kerja, Komunikasi Interpersonal Dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai SMPN 1 Plemahan Kabupaten Kediri - Nita Rismaya; Ahmad Jauhari; Nur Hidayati (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
In a agency, aspects of work morale, interpersonal communication and physical work environment will be found. This study aims to determine the role of work enthusiasm, interpersonal communication and physical work environment on employee perfomance at SMPN 1 Plemahan. This study uses quantitative methods, sampling in this study using saturated samples totaling 62 employees. Data analysis techniques used in this study are validity test, reliability test, classical assumption test, multiple liniear regression analysis, coefficient of determination, t test and F test. The results of this study indicate that 1) partially work enthusiasm has a positive and significant effect on employee perrfomance. 2) partially interpersonal communication has a positive and significant effect on employee perrfomance. 3) partially the physical work environment has a positive and significant effect on employee perrfomance. 4) simultaneously work enthusiasm, interpersonal communication and physical work environment have a positive and significant effect on employee perrfomance.